Insights from the Internet – How to Govern Outer Space - Knodel, Mallory (Global Governance of Low Earth Orbit Satellites, 2025)
Humanity has remained captivated by space exploration since the moon landing 70 years ago. As the space industry rapidly expands and more than half of US Americans believe space tourism will become a reality within the next 50 years, private companies have not yet eclipsed national efforts as essential to humanity's space future. One area where that is most apparent, practical and real is in the governance of space. Amid the complexity of our world, under dwindling rules-based liberal traditions, faced with the lack of global economic equality, multistakeholder governance and standards and systems that hold in check ground truth is crucial. This paper contributes a technical community dimension to the many scholars who have compared space and internet governance on legal and diplomatic bases. Finding a parallel in the internet– another global project – space governance might benefit from lessons learned and insights gleaned over the past few decades. At its core, effective governance in both domains requires inclusive, multistakeholder approaches, as well as unique subject matter expertise. Internet governance has demonstrated that transparency and collaboration among governments, private sector actors, civil society, and technical experts are crucial to addressing complex, global challenges. The same principles should be applied to space governance. Without a diversity of voices and perspectives, we risk reinforcing inequities and failing to anticipate the unintended consequences of new technologies.